2000
DOI: 10.1161/01.cir.101.19.2290
|View full text |Cite
|
Sign up to set email alerts
|

Prominent Role of P-Selectin in the Development of Advanced Atherosclerosis in ApoE-Deficient Mice

Abstract: Background-Adhesive interactions between leukocytes and endothelial cells are characteristic of the development of atherosclerotic lesions, but the receptors involved remain to be defined. P-selectin is an adhesion receptor expressed on activated endothelial cells or platelets and was shown to be involved in fatty streak formation in LDL receptor-deficient mice on an atherogenic diet. The main purpose of this study is to examine the role of P-selectin in the spontaneous development of advanced atherosclerosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
164
0
5

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(172 citation statements)
references
References 47 publications
3
164
0
5
Order By: Relevance
“…In case -control studies, soluble P-selectin concentrations are elevated in conditions of accelerated atherosclerosis and thrombosis (Blann et al, 2000;Frijns et al, 1997;Tsakiris et al, 1999;Xu et al, 1998). Furthermore, results of animal studies suggest that P-selectin plays a critical role in atherogenesis (Dong et al, 1998(Dong et al, , 2000. Although P-selectin is expressed on both endothelial cells and platelets, soluble P-selectin is unlikely to arise from the endothelium, and is more likely to be released from activated platelets (Blann et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In case -control studies, soluble P-selectin concentrations are elevated in conditions of accelerated atherosclerosis and thrombosis (Blann et al, 2000;Frijns et al, 1997;Tsakiris et al, 1999;Xu et al, 1998). Furthermore, results of animal studies suggest that P-selectin plays a critical role in atherogenesis (Dong et al, 1998(Dong et al, , 2000. Although P-selectin is expressed on both endothelial cells and platelets, soluble P-selectin is unlikely to arise from the endothelium, and is more likely to be released from activated platelets (Blann et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of leukocyte recruitment slows development of atherosclerosis. Indeed, P-selectin knockout mice have smaller lesions than control animals (Dong et al, 2000). NF-κB regulates expression of P-selectin and other inflammation-related genes including E-selectin, ICAM-1, VCAM-1, and MCP-1 (Cominacini et al, 1997).…”
Section: Nf-κb Response To Oxldl and Atherosclerosismentioning
confidence: 99%
“…It has been suggested that P-selectin may be involved in atherosclerosis because P-selectin deficiency delays and reduces atherosclerotic lesion formation. 7,8 Much interest has also been given to soluble P-selectin since this was first proposed to be a marker of platelet activation in 1997. 9 Recent evidence suggests that soluble P-selectin may play a key role in hemostasis and thrombosis.…”
Section: Introductionmentioning
confidence: 99%